EFEKTIVITAS EDUKASI PENCEGAHAN RISIKO JATUH TERHADAP PENINGKATAN PENGETAHUAN LANSIA - Maulidya; Dimas Sondang Irawan; Gamar (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Aging is synonymous with the elderly where the elderly experience a decline in the quality of the musculoskeletal system. In addition, the risk of falling also increases with age. This study employed a one-group pretest–posttest design and was conducted at Melati III Integrated Service Post, Community Unit 3, Bandulan, Sukun, Malang City, East Java, involving 15 elderly. Data were analyzed descriptively. The elderly experienced an increase in knowledge regarding the risk of falls, from 25% in the pre-test to 100% in the post-test. The elderly realized that providing education and physiotherapy services related to the risk of falling are essential for improving their quality of life.